Social media measurement and management : entrepreneurial digital analytics - Lipschultz, Jeremy Harris, 1958- (New York, NY : Routledge, 2020)
This new textbook applies a critical and practical lens to the world of social media analytics. Author Jeremy Harris Lipschultz explores the foundations of digital data, strategic tools, and best practices in an accessible volume for students and practitioners of social media communication. The book expands upon entrepreneurship, marketing, and technological principles, demonstrating how raising awareness, sparking engagement, and producing business outcomes all require emphasis on customers, employees, and other stakeholders within paid, earned, social, and owned media. It also looks to the future, examining how the movement toward artificial intelligence and machine learning raises new legal and ethical issues in effective management of social media data. Additionally, the book offers a solid grounding in the principles of social media measurement itself, teaching the strategies and techniques that enable effective analysis. A perfect primer for this developing industry, Social Media Measurement: Entrepreneurial Digital Analytics is ideal for students, scholars, and practitioners of digital media seeking to hone their skills and expand their bank of tools and resources. It features theoretical and practical advice, a comprehensive glossary of key terms, and case studies from key industry thought leaders.
OCLC-licensed vendor bibliographic record.
Keywords: Online social networks -- Research; Social media; Dyadic analysis (Social sciences); Social sciences -- Network analysis; Marketing research; SOCIAL SCIENCE / Media Studies